A randomized controlled trial of botulinum toxin A for treating neuropathic pain in patients with spinal cord injury. Issue 20 (May 2017) - Li, Gang; Lv, Chang-an; Tian, Li; Jin, Lian-jin; Sun, Ping; Zhao, Wei
Abstract: Background: To assess the effect of botulinum toxin A (BTA) for treating neuropathic pain in patients with spinal cord injury (SCI). Methods: A total of 44 patients with SCI with neuropathic pain were randomly divided into the intervention group and the placebo group, each group 21 patients. The subjects in the intervention group received BTA (200 U subcutaneous injection, once daily) at the painful area, whereas those in the placebo group were administered a saline placebo. This study was conducted from December 2014 to November 2016. The primary outcome was measured using the visual analog scale (VAS). The secondary outcomes were measured using the short-form McGill Pain Questionnaire (SF-MPQ), and World Health Organization quality of life (WHOQOL-BREF) questionnaire. All outcome measurements were performed before and after 4 and 8 weeks of intervention. Results: Forty-one participants completed the study. The intervention with BTA showed greater efficacy than placebo in decreasing the VAS score after week 4 and week 8 of treatment. Significant differences in the SF-MPQ and WHOQOL-BREF were also found between the 2 groups. Conclusion: The results of this study demonstrated that BTA might decrease intractable neuropathic pain for patients with SCI.